Structure of coordination motor abilities in male basketball players at different levels of competition - Sadowski, J.; Wolosz, P.; Zielinski, J.; Niznikowski, T.; Buszta, M. (Polish Journal of Sport and Tourism, 2014)
The purpose of this investigation was to examine the structure of coordination motor abilities (CMA) in male basketball players at different levels of competition. Material and methods. The study included 183 male basketball players from 10 Polish sports clubs. The examined groups consisted of seniors (n=42) aged 24.5 (± 3.3), juniors (n=37) aged 16.8 (±0.6), cadets (n=54) aged 14.5 (±0.1) and children (n=50) aged 13.4 (±0.2). A battery of motor tests was administered to assess the following CMA : kinesthetic differentiation of movements, spatio-temporal orientation, reaction time, movement coupling, sense of balance, sense of rhythm and adjustment of movements. The structure of CMA under investigation was determined based on the results of Hotelling's principal component analysis in Tucker's modification, completed with Kaiser's Varimax rotation [1, 2]. Results. The CMA structure of basketball players was composed of three or four factors. Most often these included rhythm, movement differentiation, movement coupling and adjustment of movements. Less frequently the structure consisted of spatio-temporal orientation, balance and reaction time. An in-depth analysis of the CMA structure revealed that factors ranged from heterogeneous (children and cadets) to homogeneous ones (juniors and seniors). The distribution of identified factors in the common variance was the smallest in children and cadets (58.9% and 62.9%, respectively) and the biggest in juniors and seniors (69.3% and 68.48%, respectively).